Polygenic Risk Prediction and Snca Haplotype Analysis in a Latino Parkinson S Disease Cohort - Chana-Cuevas, P (Elsevier Ltd, 2022)
Background: Large-scale Parkinson s disease (PD) genome-wide association studies (GWAS) have, until recently, only been conducted on subjects with European-ancestry. Consequently, polygenic risk scores (PRS) constructed using PD GWAS data are likely to be less predictive when applied to non-European cohorts. Methods: Using GWAS data from the largest study to date, we constructed a PD PRS for a Latino PD cohort (1497 subjects from LARGE-PD) and tested it for association with PD status and age at onset. We validated the PRS performance by testing it in an independent Latino cohort (448 subjects) and by repeating the analysis in LARGE-PD with the addition of 440 external Peruvian controls. We also tested SNCA haplotypes for association with PD risk in LARGE-PD and a European-ancestry PD cohort. Results: The GWAS-significant PD PRS had an area under the receiver-operator curve (AUC) of 0.668 (95% CI: 0.640–0.695) in LARGE-PD. The inclusion of external Peruvian controls mitigated this result, dropping the AUC 0.632 (95% CI: 0.607–0.657). At the SNCA locus, haplotypes differ by ancestry. Ancestry-specific SNCA haplotypes were associated with PD status in both LARGE-PD and the European-ancestry cohort (p-value < 0.05). These haplotypes both include the rs356182 G-allele, but only share 14% of their variants overall. Conclusion: The PD PRS has potential for PD risk prediction in Latinos, but variability caused by admixture patterns and bias in a European-ancestry PD PRS data limits its utility. The inclusion of diverse subjects can help elucidate PD risk loci and improve risk prediction in non-European cohorts. © 2022 The Authors